The Role of Tadarus Al-Qur'an in Shaping Student Character: Qualitative Study at MI Al Wathoniyah Cirebon - Yuriska Dewi Suwarno Putri; Sofyan Mustoip; Hilda Nur Azzahra; Diana Lestari, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to examine the influence of the habit of reciting the Al-Qur'an before studying on the character formation of students at MI Al Wathoniyah Cirebon City using a qualitative approach with a case study method. Data was obtained through interviews, observation and documentation involving grade 4 and 5 students, teachers and school principals. The results show that Al-Qur'an tadarus has a significant impact on character formation, such as discipline, responsibility, personal piety, a conducive learning atmosphere, and harmonious social relationships. The habit of arriving early for tadarus increases discipline, while active involvement in these activities develops student responsibility. The moral values of the Koran are internalized, honing personal piety and positive behavior such as patience, respect and gratitude. Tadarus also creates a calmer learning atmosphere, prepares students to receive lessons well, and strengthens social relationships through togetherness, creating a harmonious school environment. However, there are challenges such as lack of motivation in certain students and time constraints for implementation. In conclusion, the habit of tadarus Al-Qur'an contributes positively to the formation of student character, is relevant as a superior educational program based on Islamic values, and can be a reference for other educational institutions in building student character holistically.